PENGARUH TIME REPETITION (TR) DAN FLIP ANGLE (FA) TERHADAP INFORMASI ANATOMI PADA 3D TOF MRA PEMERIKSAAN BRAIN DENGAN MRI 1.5 TESLA - Muhamad Marno Alamsyah; Rasyid Rasyid; Emi Murniati (Perhimpunan Radiografer Indonesia (PARI), 2020)
Background: In MR angiography examination of the brain, there are many clinical situations where radiologist want to optimal suppression of stasionary nuclei. So stasionary nuclei and flowing nuclei will produce a good contrast. One of the most commonly used method MR angiography of the brain is a 3D TOF because it can show the blood vessels by hyperintens with more hypointens of background. Parameters TR and flip angle is one of the parameters that will determine a stasionary nuclei experiencing suppression well and the flowing nuclei will still generate a signal that more hyperintens. The porpose of this study was to determine the influence of repetition time and flip angle of the anatomical information of 3D TOF MRA examination of the brain, and also to determine value the repetition time and flip angle best to display anatomical information of 3D TOF MRA examination of the brain. Methods: This research is an experimental approach to the pre-experimental research design and post-test only research design. This research was conducted in Bintaro Premier Hospital. The data in the form of 54 3D TOF MRA images brain of 6 volunteers with nine variations repetitions time and flip angle. Assessment anatomical information performed by the two respondents or reviewer. The data analysis is done by testing the influence is multiple linear regression to determine the value of repetition time and flip angle optimal use friedman mean rank test. Result: The result showed that there is the influence of repetition time and flip angle of the anatomical information on 3D TOF MRA examination of the brain with a significance level of p <0.001 (p <0.05). The repetition time 30 ms and flip angle 30o is and optimal value for anatomical information showing 3D TOF MRA examination of the brain. application of repetition time 30 ms and flip angle 30o can be properly saturate or suppression the stasionary nuclei so that is displays excellent contrast between the nuclei. Conclution: There are influence of repetition time and flip angle to the anatomical information on 3D TOF MRA examination of the brain with a significance level of p <0.001 (p <0.05). The repetition time 30 ms and a flip angle of 30o is an optimal value for anatomical information showing 3D TOF MRA examination of the brain.